Microvascular decompression for intermediate nerve neuralgia: a case report and literature review - Wang, Kan; Li, Wenhao; Bo, Yujie; Li, Biao; Wan, Jinxin; Mu, Luyan; Song, Yuwen (Frontiers in Surgery, 2024)
Intermediate nerve neuralgia (INN) is a rare craniofacial pain syndrome. The diagnosis of INN is challenging because of the complex ear sensory innervation, which results in clinical overlap with both trigeminal neuralgia (TN) and glossopharyngeal neuralgia (GPN). A 76-year-old woman with a remarkable medical history presented with right otalgia and mandibular pain for seven years. Neurological examination revealed diminished sensation in the distribution of the intermediate nerve. Magnetic resonance imaging demonstrated an impression of the anterior inferior cerebellar artery (AICA) on the facial-vestibulocochlear nerve complex (VII/VIII complex). The patient underwent microvascular decompression (MVD) after long-term oral medication. We confirmed that the responsible vessel was close to the VII/VIII complex and isolated the vessel under the microscope via a right-sided suboccipital retrosigmoid approach. The patient's otalgia and mandibular pain disappeared after operation. There were no additional neurological deficits. MVD is a safe and feasible option for patients with Intermediate nerve neuralgia who have failed to respond to an adequate pharmacotherapy.